Diagnosing Dutch Disease : Does Russia Have the Symptoms? - Kalcheva, Katerina (IMF Working Papers; Working Paper ;, 2007)
In this paper, we assess whether recent economic developments in Russia are symptomatic of Dutch Disease. We first provide a brief review of the literature on Dutch Disease and the natural resource curse. We then discuss the symptoms of Dutch Disease, which include (1) real exchange rate appreciation; (2) slower manufacturing growth; (3) faster service sector growth; and (4) higher overall wages. We test these predictions for Russia while carefully controlling for other factors that could have led to similar symptoms. We conclude that, while Russia has all of the symptoms, the diagnosis of Dutch Disease remains to be confirmed.